A Novel, Weakly N‐Doped Cathode‐Modifying Layer in Organic Solar Cells. Issue 8 (3rd June 2021) - Chen, Chunxin; Xue, Peiyao; Lu, Heng; Wang, Jiayu; Jia, Boyu; Li, Yawen; Qin, Dashan; Lin, Yuze; Zhan, Xiaowei
Abstract : A novel blend thin film ( N, N ‐dimethyl‐ammonium N ‐oxide)propyl perylene diimide mixed with polyethylenimine ethoxylated (PDINO:PEIE) is provided as a cathode‐modifying layer (CML) in organic solar cells (OSCs). Compared with PDINO, PDINO:PEIE shows increased electron conduction, due to the weak n‐doping of PDINO by the amino groups of PEIE, improving the balance of hole/electron mobility and thereby the fill factor of the device. Moreover, the addition of PEIE in PDINO enables a smoother morphology of the device and helps block the cathode diffusion into the photoactive layer, reducing trap‐assisted recombination in the exciton formation zone and thereby, increasing the open‐circuit voltage of the device. As a result, PDINO:PEIE enables greater power conversion efficiency (PCE) of fullerene OSCs than PDINO. It is also shown that, relative to conventional CMLs, PDINO:PEIE presents higher PCEs and comparable stabilities of nonfullerene OSCs. The blend thin films containing the small‐molecular host and weak polymeric n‐dopant are promising CMLs to integrate high electron mobility, good film‐forming property, low recombination loss, no migration of counter ions, and good stabilities. Abstract : A novel, weakly n‐doped cathode‐modifying layer (CML) PDINO:PEIE, featuring the small‐molecular host mixed with weak polymeric n‐dopant, is provided. Compared with PDINO, PDINO:PEIE improves the hole/electron mobility balance and suppresses trap‐assisted recombination in the exciton formation zone. Relative to conventional CMLs, PDINO:PEIE exhibits higher efficiencies and comparable stabilities of nonfullerene‐based organic solar cells.